Geopolitics : a very short introduction - Dodds, Klaus (Colección de libros electrónicos de ULoyola, 2014)
Geopolitics is a way of looking at the world: one that considers the links between political power, geography, and cultural diversity. Using examples ranging from historical maps and 007 films to the rhetoric of political leaders, Klaus Dodds shows why, for a full understanding of contemporary global politics, it is essential to be geopolitical. - ;Geopolitics is a way of looking at the world: one that considers the links between political power, geography, and cultural diversity. In certain places such as Iraq or Lebanon, moving a few feet either side of a territorial boundary can be a matter.